The yeast protein interaction network has a capacity for self‐organization. (1st July 2014) - Dhroso, Andi; Korkin, Dmitry; Conant, Gavin C.
<x xml:space="preserve">Abstract</x> The organization of the cellular interior gives rise to properties including metabolic channeling and micro‐compartmentalization of signaling. Here, we use a lattice model of molecular crowding, together with literature‐derived protein interactions and abundances, to describe the molecular organization and stoichiometry of local cellular regions, showing that physical protein–protein interactions induce emergent structures not seen when random interaction networks are modeled. Specifically, we find that the lattices give rise to micro‐groups of enzymes on the surfaces of protein clusters. These arrangements of proteins are also robust to protein overexpression, while still showing evidence for expression tuning. Our results indicate that some of the complex organization of the cell may derive from simple rules of molecular aggregation and interaction.